Obstacles of Professional Management in Football Professional League Club in Kingdom of Saudi Arabia - Alqahtani, Abdulaziz Muflih (Πανεπιστήμιο Πελοποννήσου, 2016)
Title Obstacles of professionalism management in football professional league club in Kingdom of Saudi Arabia. The objectives of the study The basic purpose of this study is to identify the most importance Obstacles of professionalism management in football professional league club in Kingdom of Saudi Arabia. Methodology The research sample was selected in intentional random method , the total number of the sample was 70 individual of ( owners, managers ) . The researcher used in the statistical process the computer program SPSS and he used the following processes Descriptive statistics (mean, standard division ,percentage and analytical statistics( correlation coefficient, Cronbach's Alpha). The most important results of the study The researcher reached that the first axis “ obstacles related with administrative aspect “ the phrase is “ the special rules of Saudi professionalism suitable with the rules of international federation “ it came first with 97.39 % , the phrase “ the special rules of Saudi professional suitable with the same rules of advanced countries in the process of professionalism in football “ came second with 80.00 % the second axis “obstacles related with financial aspect the phrase the facilitation of regular repayment of the club obligations from professionalism administration and phrase supporting the begging of privatization of professional administration to achieve the professional aims the phrase the values of players contracts balanced with club budget which facilitate the work of professionalism administration came first with 100 %. The study concluded that there are various needs for the staff working in the professionalism field in Saudi Arabia. They also need to work to a plan and timetables. There should be also planned objectives for the Saudi professionalism. There is also shortage in the finance for applying professionalism with an international style. There is also a dire need to apply innovative rules and regulations to keep pace with new updates that takes place in professionalism, in addition to regulating training courses to the staff working in professionalism. Recommendations The most important recommendations of a questionnaire management professionalism League clubs for football in Saudi Arabia to assess the performance of management professionalism_, develop strategic plans for the Saudi system of professionalism and in accordance with the methods and scientific methods for football, set goals for professional system in Saudi Arabia.
Keywords: Soccer - Management - Saudi Arabia; Professional sports - Management - Saudi Arabia; Soccer - Economic aspects - Saudi Arabia; Ποδόσφαιρο - Διοίκηση και Οργάνωση - Σαουδική Αραβία; Επαγγελματικός αθλητισμός - Διοίκηση και Οργάνωση - Σαουδική Αραβία; Ποδόσφαιρο - Οικονομικές απόψεις - Σαουδική Αραβία; Sports professionalism; Professionalism Management; Professional football Player; Amateur Player; Επαγγελματισμός στον αθλητισμό; Οργάνωση και διαχείριση του επαγγελματισμού; Επαγγελματίας ποδοσφαιριστής; Ερασιτέχνης ποδοσφαιριστής